The Efficacy and Tolerability of Selective Serotonin Reuptake Inhibitors for Motor Recovery in Non-depressed Patients After Acute Stroke: A Meta-Analysis - Su, Ning; Wen, Changming; Guo, Shiqian; Yu, Yang; Wang, Chenglin (Frontiers in Neurology, 2021)
Objective: To explore the efficacy and tolerability of selective serotonin reuptake inhibitors(SSRIs) for motor recovery in non-depressed patients after acute stroke. Methods: According to the predefined retrieval strategy, multiple electronic databases were searched for randomized controlled trials(RCTs) that met the inclusion criteria. The primary efficacy outcome was measured by Fugl-Meyer Motor Scale(FMMS) score and the indicators of tolerability included withdrawal rate and the incidence of adverse events(AEs). Results: 10RCTs were included, the pooled analyses showed patients who received fluoxetine (endpoint: MD=21.17, 95%CI 14.13 to 28.21, P<0.00001; mean change: MD=16.27, 95%CI 10.05 to 22.50, P<0.00001) and citalopram (endpoint: MD=22.93, 95% CI 11.13 to 34.73, P=0.0001; mean change: MD=24.06, 95% CI 10.47 to 37.65, P=0.0005) experienced greater improvement in FMMS score. There was no evident difference in total withdrawal rate (fluoxetine: OR=1.11, 95%CI 0.90 to 1.27, P=1.38; citalopram: OR=0.94, 95%CI 0.69 to 1.28, P=0.71; escitalopram: OR=0.87, 95%CI 0.58 to 1.28, P=0.47) between two groups. Besides, the incidence of hyponatremia (OR=2.01, 95%CI 1.16 to 3.50, P=0.01), seizure (OR=1.46, 95%CI 1.03 to 2.08, P=0.04) and fracture (OR=2.34, 95%CI 1.61 to 3.40, P<0.00001) in the fluoxetine group was higher than in the placebo group. Conclusions: Fluoxetine and citalopram can promote motor recovery in non-depressed patients with acute stroke, but it is necessary to pay attention to the possible AEs of fluoxetine, such as hyponatremia, seizure and fracture.